2022
DOI: 10.1093/jrr/rrac025
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome of cervical cancer patients treated by image-guided brachytherapy: a ‘real world’ single center experience in Thailand from 2008 to 2018

Abstract: The objective of our study was to evaluate the survival outcome of cervical cancer patients treated using image-guided brachytherapy (IGBT). From 2008 to 2018, 341 patients with cervical cancer were treated by radical radiotherapy. IGBT (by computed tomography [CT] or transabdominal ultrasound [TAUS]) was used to treat all of these patients. The characteristic data and patient status after treatment were recorded. All data were evaluated for survival outcome analysis. From a total of 341 patients, 295 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…While some of our findings are consistent with previous research, particularly regarding the importance of tumor stage, there are discrepancies. For example, histopathology shows different outcomes in our study compared to those reported in the study by Tharavichitkul et al [ 22 ]. The insights gained from this research could assist in the planning and resource allocation for patient care.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…While some of our findings are consistent with previous research, particularly regarding the importance of tumor stage, there are discrepancies. For example, histopathology shows different outcomes in our study compared to those reported in the study by Tharavichitkul et al [ 22 ]. The insights gained from this research could assist in the planning and resource allocation for patient care.…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, direct comparisons with our study, which concentrates on predicting survival time, are not feasible. However, based on research results in the same field, the performance of prediction models built for both classification and regression is known to be relatively accurate [9,[18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight cervical points were defined by TAUS and marked on the orthogonal images to serve as reference points to guide the dose optimization. In their report of 295 patients over ten years who underwent CT-or TAUS-guided BT, there were no significant differences between the two modalities in terms of local control and survival [58].…”
Section: Us-guided Bt: Promising and Low-costmentioning
confidence: 96%
“…This practice has reported very low rates of ≥3 and adverse events, demonstrating the safety of the procedure, and further attempts will be made to apply hybrid applicators to improve target coverage [56]. Tharavichitkul et al [58,75] reported their experiences and excellent outcomes of dose planning using TAUS and orthogonal radiographs. Eight cervical points were defined by TAUS and marked on the orthogonal images to serve as reference points to guide the dose optimization.…”
Section: Us-guided Bt: Promising and Low-costmentioning
confidence: 98%